Kepastian Hukum Pendaftaran Tanah Secara Sporadik Oleh Kantor Pertanahan Yang Menimbulkan Sertifikat Ganda - Adhi Kurniawan; Wira Franciska; Dhody AR Widjajaatmadja (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
In the first land registration, the phrase cadastral registration, a technical term for recording records, land registration, ownership of rights, rechkadastral, and legal cadastral, is governed by government regulation 10 of 1961. In occasional land registration, BPN does not employ competent administration, resulting in administrative flaws that might lead to duplicate certificates for land parcel owners. To obtain legal certainty over the physical and legal ownership of land parcels in the ownership of the certificate of title and to apply the muthakir principle, the ownership of the certificate is doubled because Bpn's registration does not use the most recent principle in sporadic land registration for the first time. This study employs normative juridical research, namely library law research or secondary data with primary, secondary, and tertiary legal sources, as well as interviews with district-city measurements. Land registration must have a foundation, namely a land book, so that the landowner's ownership has legal certainty that stays valid on the land's physical surface with a legal certificate of ownership, namely a certificate. The conclusion is that in the issuance of double certificates, legal remedies may be settled through non-litigation, mediation between the aggrieved party, the land owner, and the National Land Agency (Non Litigation), and if this is not possible, through court (litigation) peace and tax restitution.